ANALISIS KANDUNGAN E-COLI DAN TOTAL COLIFORM KUALITAS AIR BAKU DAN AIR BERSIH PAM MANADO DALAM MENUNJANG KOTA MANADO YANG BERWAWASAN LINGKUNGAN - Tia Milka Rompas; Wiske Ch. Rotinsulu; J.V. Bobby Polii (COCOS, 2018)
ABSTRACT This research was conducted for 3 months, from March to May 2017. The water sampling location was selected at two points. The first location was in TONDANO River (the river around PT Air Manado). The second was clean water at PT Air Manado. The water sampling was collected with three replications (sampling time) and analysed at in Manado Baristan laboratory. This research aimed to know the content of E-Coli and Total Coliform in a standard water and a clean water of PT. Air Manado. The results showed that the content of E-Coli and Total Coliform in Tondano River were lower the standard quality of 5000 (number/100 ml); For the first sampling, intake E-Coli 13/100 ml, Total Coliform 14/100ml; the second sampling, E-Coli 1.8/100ml, Total Coliform 340/ 100ml and the third sampling, E-Coli 0/100ml, Total Coliform 240/100ml. All water sample has met the water quality standard according to Government Decree Number 82, 2001 about water quality treatment and water pollution control. As for the clean water samples, the results showed that the first and the second samples have not met the quality standard for clean water as they have E-Coli and Total Coliform (First sampling, E-Coli 4/100ml and Total Coliform the first sample 2 /100ml; The second sampling, E-Coli 0/100 ml and are Total Coliform4/100ml. Keyword : Clean Water, E-Coli, Total Coliform.